THE INFLUENCE OF LEADERSHIP STYLE AND WORK ENVIRONMENT ON THE PERFORMANCE OF LG BANDAR LAMPUNG RESTAURANT EMPLOYEES - Novia Nafa Wilona; Defrizal Defrizal (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The success and sustainability of activities within a company to produce the desired results, depends on the human resources that exist within the company itself. This study was conducted to find out whether there is an influence of leadership style on employee performance, whether the work environment affects employee performance, and whether there is an influence of leadership style and work environment on employee performance of LG Bandar Lampung Restaurant. The method in this study uses a quantitative approach and SPSS program version 25 as a tool to analyze data. The independent variables in this study are Leadership Style (X1) and Work Environment (X2), while the dependent variable is Performance (Y). The population and sample are employees of LG Bandar Lampung Restaurant which amounted to 30 people. This study proves that partially leadership style does not have a significant influence on employee performance variables. While work environment variables have a positive influence on employee performance variables. Simultaneously, variable X (leadership style and work environment) together affect variable Y (employee performance).